Modeling and computational simulation of Piptocoma discolor (Pigüe) fluid for combustión optimization in Ecuador - Gonzalez, Juan; Oliva M, Deny; Zambrano Vera, David; Darío Ledesma, Rubén; Bonilla, Mario Jorge; Casco G, Erika Clara; Zúñiga, Édison Ernesto (Enfoque UTE, 2022)
Computational modeling and simulation represents a competitive and functional tool that effectively supports the study of thermochemical behavior in combustion optimization, guaranteeing reliable results through modeling, design and allowed the validation of excess thermodynamic properties applied for combustion. of the biomass of Piptocoma discolor (pigüe) from the Amazonian region of Ecuador and Latin America. The model parameters were physical, chemical and thermal through computational fluid dynamics in combustion optimization. And the mathematical model of combustion was obtained under the transport method of the species. In the simulation, the variables of primary air flow and moisture content were observed. The variable of the combustion parameters were N2, O2, CO, H, pressure, temperature, humidity, total energy and burning time of the biomass particles. The geometric configuration was developed according to the fundamental principles of CFD within Ansys Fluent to obtain the behavior of speed, turbulence, pressure, etc. of the composition of the optimal fuel 91.75% of a complete combustion and compared to other species that show 86% of the reactions of the combustion of the species.